Autonomous Mobile Robot Power Management System - Al-Qdah, Malik Taysir (1999)
The most important part of an autonomous mobile robot is its power management in order to avoid any deadlock. A system was developed to identify the time when the autonomous mobile robot needed to return for battery recharge through an alarm of the battery error detection. The design of this system is a car-like mobile robot with two front steering wheels and two rear driving wheels. The steering gear motor turns the entire front-wheel assembly a number of degrees to the left or right of the straight-ahead. The drive motor is mounted to one of the rear wheels and both rear wheels are fixed to the rear axle. The gear motor can drive both of them at the same time. This mobile robot is kinematically constrained body, which can be modelled as a 2D object translating and rotating in the horizontal plane. The discharge parameters are the battery voltage and the battery capacity. The values of these two discharge parameters are function of the battery suitability to the load. Using a microcontroller-based circuit with current and temperature sensors did achieve the battery management process. The battery temperature and voltage sensors provide information for the changed battery status. The current sensor monitors the current delivered from the battery during the discharge time. From identifying the value of the current, the applied load to the mobile robot can be known. From the sensed current the system can generate a suitable countdown time to estimate the remaining battery lifetime under load. The time is updated as the load is changed.